PENGEMBANGAN MODUL BERBASIS PENDEKATAN KONTEKSTUAL PADA MENULIS RESENSI DI KELAS IX SMP 7 PADANG BOLAK - Jusrin Efendi Pohan; Atmazaki .; Agustina . (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: This research aimed to produced the module based context model of writing review material. The development of the modul model were grounded by a crucial problem, students have a low ability in writing the review by productive teaching facility or the teaching material, the teacher tend to deliver the material based on memorize context, not a synthetic thinking, so that the students fell bored and annoyed, and the teaching material was not focused in increasing students ability. Kind of this research is research and development. Research procedure used ADDIE model is Analysis, Design, Development, Implementation, and Evaluasi. Module draft developed then validated by three expert judgement. After module in validated, the module stride was tested on student at Class IX SMP 7 Padang Bolak. The data obtained to be analyzed descriptively. This research found that (1) module based context of writing review material which was developed, (2) module based context of writing review have been practice to use in writing review leraning, and (3) module based context of writing review have been effective in increasing student activities and motivations on studied writing learning. Keywords: module; writing review material; ADDIE model.